Molecular Imaging of Metabolic Reprograming in Mutant IDH Cells - Viswanath, Pavithra; Chaumeil, Myriam M.; Ronen, Sabrina M. (Frontiers in Oncology, 2016)
Mutations in the metabolic enzyme isocitrate dehydrogenase (IDH) have recently been identified as drivers in the development of several tumor types. Most notably, cytosolic IDH1 is mutated in 70-90% of low-grade gliomas and upgraded glioblastomas, and mitochondrial IDH2 is mutated in ~20% of acute myeloid leukemia cases. Wild-type IDH catalyzes the interconversion of isocitrate to α-ketoglutarate (α-KG). Mutations in the enzyme lead to loss of wild-type enzymatic activity and a neomorphic activity that converts α-KG to 2-hydroxyglutarate (2-HG). In turn, 2-HG, which has been termed an “oncometabolite”, inhibits key α-KG- dependent enzymes, resulting in alterations of the cellular epigenetic profile and, subsequently, inhibition of differentiation and initiation of tumorigenesis. In addition, it is now clear that the IDH mutation also induces a broad metabolic reprogramming that extends beyond 2-HG production, and this reprogramming often differs from what has been previously reported in other cancer types. In this review we will discuss in detail what is known to date about the metabolic reprogramming of mutant IDH cells and how this reprogramming has been investigated using molecular metabolic imaging. We will describe how metabolic imaging has helped shed light on the basic biology of mutant IDH cells and how this information can be leveraged to identify new therapeutic targets and to develop new clinically translatable imaging methods to detect and monitor mutant IDH tumors in vivo.